청각장애인을 위한 청능훈련 서비스모델 및 기능성 게임콘텐츠 설계 - 박화진(Hwa-Jin Park) (디지털콘텐츠학회논문지, 2011)
청각장애인을 위한 청능 및 언어 훈련은 비장애인과 소통능력을 배양하는 기본적인 훈련이지만 동시에 부모나 지도교사의 경제적부담, 육체적 피로를 수반한다. 이를 해결하기 위해 웹기반의 청능 및 언어 훈련 콘텐츠가 계속해서 개발되어 왔다. 그러나 장애인의 청각상태 및 학습능력의 차이가 존재함에도 불구하고 이런 개인 차이를 고려하지 않은 채 개발되고 있다. 따라서 장애자의 상태와 잔존청력, 학습능력 및 훈련성취도를 정확히 평가하고 분석하여 장애자에게 적절한 훈련진도를 계획하는 것이 중요하다. 본 논문에서 청각장애자를 위해 개인평가에 따라 다양하게 청능 언어 훈련을 기획하고 관리해주는 청능 및 언어 훈련 서비스 모델을 제안한다. 또한 이 모델을 기반으로 하는 기능성 게임콘텐츠를 기획하는 설계방법을 제시한다. Auditory and language train for the hearing-impaired is an essential course improving conversational capability with non-deaf and accompanying the financial burden and the physical fatigue of parents or a teacher. To reduce these problems, web-based training contents have been developed. But these contents have been developed without consideration of individual difference such as various levels of residual hearing and the learning capability of hearing-impaired. Therefore, it is important that appropriate training progress for each hearing-impaired should be designed by evaluating and analyzing the personal status, residual hearing, learning capability and training achievement. This paper suggests auditory and language training service model for the hearing-impaired, which is planning and managing an auditory and learning training based on personal evaluation. In addition, this paper suggests a design method for a serious game content planing based on this service model. KCI Citation Count: 6